Genetic analysis of acute intermittent porphyria caused by novel classical splicing variant in the insertion region of 29-residue specific to human HMBS protein - Liang, Lei; Meng, Haixia; Wu, Haotian; Zhao, Jianrong (Frontiers in Molecular Biosciences, 2023)
Background: Acute intermittent porphyria (AIP; OMIM#176000) is a genetic disorder that is caused by mutations in the hydroxymethylbilane synthetase (HMBS) gene. This gene encodes the third enzyme in the heme biosynthesis pathway. Human HMBS (hHMBS) contains a 29-residue insert (residues 296-324) at the interface between domains 1 and 3. The function of this insert is currently unknown. In this study, a previously unidentified classical Splicing variant was discovered in the HMBS gene of a female AIP patient from China. The variant was validated through comparison with the patient's husband and daughter. Methods: Peripheral blood samples were obtained from the patient, the patient's husband, and their daughter. Gene expression was analyzed using whole exon sequencing and Sanger sequencing. To validate alternative splicing, RNA was extracted from the patient's peripheral blood and reverse transcribed into cDNA. Aberrant splicing caused by variants was predicted using I-TASSER and PyMOL software to simulate protein structures. Finally, molecular dynamics of the proteins were simulated using the AMBER14sb software. Results: The patient and her daughter have a classical Splicing variant c.912+1G>C of the HMBS gene. This variant was not found in the patient's husband and has not been previously reported in scientific literature. Analysis of the patient's peripheral blood transcripts revealed that c.912+1G>C retained intron 13 and resulted in an exon 13 skipping. Further analysis through homology modelling and molecular dynamics showed that this variant alters the secondary structure of the HMBS protein, leading to functional differences.This research has discovered a new classical Splicing variant c.912+1G>C in the HMBS gene that has been identified as pathogenic. This finding not only expands the molecular heterogeneity of AIP but also provides crucial information for genetic diagnosis.